Hubungan Pengetahuan, Sikap, Tindakan Gaya Hidup Sehat dengan Pasien Diabetes Mellitus Tipe 2 di Klinik Budhi Pratama Restu Ibu Jakarta Tahun 2022 - Muhamad, Gilang Sukma; Budiharto, Budiharto; Trisuci A, Yuna (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
Diabetes mellitus (DM) is one of the chronic metabolic diseases that is still a global concern today. DM prevalence in the DKI Jakarta province is the highest in Indonesia, which is 3.4% (Riskesdas, 2018). The description of knowledge, attitudes, and practices of the community towards DM is very important for research to determine programs to prevent increased morbidity and mortality due to DM. Study objective to explain the relationship between knowledge, attitudes, practices about a healthy lifestyle with blood sugar control of DM patients at the Budhi Pratama Restu Ibu Clinic, East Jakarta and the most influential dominant factors. Methods used was Cross sectional analytic descriptive research. Sample was 86 participants of Prolanis DM. Respondents were given a Knowledge, Attitude, and Practice questionnaire about a healthy lifestyle. Fasting Blood Glucose (FBG) data was taken from medical records. Data analysis with chi-square and logistic regression backward LR model. Results showed weak correlation between knowledge  (p = 0.005), there is no correlation between attitudes  (p = 0.107), and significant correlation between practices and blood sugar control of DM patients (p = 0.000). Practice is the dominant factor that affects the regression coefficient = 0.000. Knowledge and practices about a healthy lifestyle are associated with blood sugar control of DM patients. We suggest further research comparing Prolanis participants and non-participants.Keywords : knowledge, attitude, practices, healthy lifestyle, fasting blood glucose,  diabetes mellitus